Pendidikan Agama Dalam Perkembangan Karakter Anak Usia Dini (AUD) - Leni Diani; Siti Masyithah (Indonesian Publication Center, 2024)
Religious education has a significant role in the formation of early childhood character (AUD). This study aims to explore the influence of religious education on the development of children's character in moral and ethical aspects and identify effective teaching methods in religious education. The research method used is qualitative descriptive, involving interviews, observations, and documentation studies in early childhood education institutions. The results of the study show that religious education can increase positive values such as honesty, responsibility, and empathy, as well as contribute to children's social behavior. Interactive and fun teaching methods, such as games and visual media, have proven to be effective in helping children understand and apply religious teachings. This finding is expected to provide recommendations for educators and parents in an effort to improve the quality of religious education in children's environments, so that they can form a generation with noble character and be able to contribute positively in a multicultural society.